Krisendeutungen: Die aktuelle Mediendebatte um den öffentlich-rechtlichen Rundfunk - Scheufele, Bertram; Jost, Arietta, M.A.; Spachmann, Klaus (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Is there a crisis of public service broadcasting? This book views public service broadcasting rather prosaically as a research object. After systematising different approaches to public service broadcasting in communication science, the authors define their concept of a crisis interpretation and study empirically which typical crisis interpretations are prevalent in the current media debate on public service broadcasting. Finally, the authors discuss the mindsets and the calls for action in relation to these crisis interpretations as well as their shortcomings. This book is intended to contribute to an unbiased analysis of public service broadcasting.